2020
DOI: 10.1142/s108842462050011x
|View full text |Cite
|
Sign up to set email alerts
|

Optical limiting properties, structure and simplified TD-DFT calculations of scandium tetra-15-crown-5 phthalocyaninates

Abstract: The optical limiting properties of crown-ether-substituted scandium(III) phthalocyaninate complexes, bis-tetra-15-crown-5-phthalocyaninates Sc[(15C5)4Pc][Formula: see text] (I) and Sc[(15C5)4Pc][Formula: see text] (Ia), together with monophthalocyaninate [(15C5)4Pc]Sc(OAc) (II) were measured by using the Z-scan technique (532 nm laser and pulse rate of 10 ns). It was revealed that expansion of the [Formula: see text]-system on moving from the monomeric Sc complex II to sandwich compound I and changing the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Dispersion correction D3BJ was included. It has been previously found to be particularly important to reproduce the deformations of macrocyclic ligands in sandwich Pc complexes. , The observed consistency between the X-ray and DFT data suggests that an increase in the distance between the substituted Pc ligands occurs because of the repulsion rather than the intercalation of K ions.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Dispersion correction D3BJ was included. It has been previously found to be particularly important to reproduce the deformations of macrocyclic ligands in sandwich Pc complexes. , The observed consistency between the X-ray and DFT data suggests that an increase in the distance between the substituted Pc ligands occurs because of the repulsion rather than the intercalation of K ions.…”
Section: Resultsmentioning
confidence: 63%
“…It has been previously found to be particularly important to reproduce the deformations of macrocyclic ligands in sandwich Pc complexes. 33,34 The observed consistency between the X-ray and DFT data suggests that an increase in the distance between the substituted Pc ligands occurs because of the repulsion rather than the intercalation of K ions. Such an analysis became possible because of the correlation between the predominantly dipolar lanthanide-induced shift [LIS; Δδ p , eq 1] and the structure of the complexes: this…”
Section: ■ Results and Discussionmentioning
confidence: 77%
“…In the absence of this correction, geometrical optimization of sandwich phthalocyaninates lead to structures with severely concaved Pc ligands which clearly contradicts X-ray data [ 47 ]. On the other hand, it has already been reported that the applied D3BJ correction overestimates the stabilisation of the g -conformations of alkoxy-substituted sandwiches even in cases where such conformation can be excluded on the basis of experimental data [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the N (290 nm), Soret or B (300-400 nm) and Q (670-680 nm) bands are typical for phthalocyanines in general, the additional absorbances at 480-490 (blue valence bands, BV), 910-920 (red valence bands, RV) and 1400-1600 nm (intervalence bands, IV) are characteristics of double-decker complexes containing one unpaired electron [28,35,36]. The positions of all bands in the spectra of series of complexes gradually shift following the decrease in lanthanide ions radius causing the increase in intramolecular π-π interaction [37].…”
Section: Resultsmentioning
confidence: 99%